2020
DOI: 10.1039/c9ra10256f
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of a BiOClxBr1−x nanostructure photocatalyst with high surface area for the enhanced visible-light photocatalytic reduction of Cr(vi)

Abstract: Cr(vi) reduction is performed by BiOCl0.8Br0.2 composite produced via a facile in situ synthetic process at room temperature while making use of PVP (Mw = 10 000).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 40 publications
(50 reference statements)
3
10
0
Order By: Relevance
“…The Bi/ BiOCl 0.8 Br 0.2 film had the lowest emission intensity among the as-prepared Bi/BiOCl x Br 1−x films as a result of the synergic effect of its 3D flower-like nanostructure, the formation of Bi/ BiOCl x Br 1−x heterojunction, and the presence of oxygen vacancies, leading to a longer lifetime of the charge carriers. [18,42] This observation was further confirmed by recording the photocurrent of the as-prepared films. Generally, a stronger photocurrent response suggests the effective separation of photogenerated electron-hole pairs.…”
Section: Optical and Photoelectrochemical Analysissupporting
confidence: 57%
See 2 more Smart Citations
“…The Bi/ BiOCl 0.8 Br 0.2 film had the lowest emission intensity among the as-prepared Bi/BiOCl x Br 1−x films as a result of the synergic effect of its 3D flower-like nanostructure, the formation of Bi/ BiOCl x Br 1−x heterojunction, and the presence of oxygen vacancies, leading to a longer lifetime of the charge carriers. [18,42] This observation was further confirmed by recording the photocurrent of the as-prepared films. Generally, a stronger photocurrent response suggests the effective separation of photogenerated electron-hole pairs.…”
Section: Optical and Photoelectrochemical Analysissupporting
confidence: 57%
“…The Bi/BiOCl 0.8 Br 0.2 film exhibited the highest photocurrent responses compared to its counterparts, highlighting its outstanding separation of the photoinduced charge at the interface and thus its superior photocatalytic performance. [ 18 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the enhanced photoreduction of Cr(VI) in the presence of irradiated BiOX could be attributed to the strong adsorption on the photocatalyst's surface, which was obtained by the use of mannitol for synthesis. The previously reported surfactants addition to the BiOX synthesis [35,52] and BiOX modifications [53] did not elevate the Cr(VI) adsorption on the photocatalyst surface to such an extent. Based on the results obtained, it could be concluded that the mannitol used in the synthesis as a template and capping agent played a crucial role in the exposure of (110) plane of BiOX (X = Cl, Br, I) and the creation of defects.…”
Section: Photocatalytic Activitymentioning
confidence: 65%
“…19,20 In addition, within ion doping, selfdoping of halogens (Cl, Br, I) is an effective method to strengthen the visible light utilization and overcome the drawback of the high recombination rate of electron-hole pairs. In particular, BiOM x R 1Àx (M, R ¼ Cl, Br, I) composite systems have been recently synthesized, such as BiOCl x I 1Àx , 21 BiOBr x I 1Àx , 22 BiOCl x Br 1Àx , 23,24 BiOI x Br (1Àx) 25 and BiO(ClBr) (1Àx)/2 I x , 26 which showed higher photocatalytic activities than the corresponding single components. For instance, Jia et al synthesized a solid solution of BiOBr x I 1Àx and demonstrated its visible-lightinduced photocatalytic properties.…”
Section: Introductionmentioning
confidence: 99%